A quantitative analysis of Malaysian secondary school technology leadership - Mohd Hamzah, Mohd Izham; Nordin, Norazah; Jusoff, Kamaruzaman; Abd. Karim, Rusnah; Yusof, Yusma (Canadian Research & Development Center of Sciences and Cultures, 2010)
Effective school administrators are keys to large-scale, sustainable education reform. Rapid changes in technology have led to new possible ways for managing and leading schools. Leadership within the context of these changes becomes a crucial agenda among school leaders all over the world. Technology Leadership is seen as the relationship between leadership and technology, whereupon the administrators must play a more proactive role in implementing technology, and more specifically strive to interface the human and information technology components. Many point to the problem of overemphasis on the technological aspect at the exclusion of the human resources function. The use of a Model of Technology Leadership, which is based on the standard set by National Educational Technology Standard for Administrators (NETS-A, 2002), is proposed. NETS-A, 2002, was initiated by International Society for Technology in Education. This paper discusses both the model and standards mentioned. It also explores the concept of Technology Leadership against the backdrop of current structure and processes in the education institution. It also reports on the findings of a survey on Administrators as Technology Leaders among 63 administrators of Secondary Schools in Negeri Sembilan. The findings explored show the existence of Technology Leadership elements in school; but school administrators scored average on the Leadership and Vision and Teaching and Learning variables and below average on the Productivity and Professional Practice variable. The t-test scores revealed that neither school location nor administrators' gender significantly influence the level of technology leadership.